“Die grosse Zeit ist vorüber”. Uddrag af H.O. Langes korrespondance med Georg Steindorff 1937-1939 - Pedersen, Lars Schreiber (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2017)
Lars Schreiber Pedersen: “Die grosse Zeit ist vorüber”. Extract from H. O. Lange’s correspondence with Georg Steindorff 1937-1939 During his first stay at the home of Professor Adolf Erman in Berlin in 1887, the Danish Egyptologist, H. O. Lange (1863-1943) also got to know a number of Erman’s students. The oldest of them was Georg Steindorff (1861-1951), with whom Lange developed a long, friendly relationship, which was to last for over 50 years. Based on the archive material from the Royal Library in Copenhagen and the Egyptian Museum at the University of Leipzig, this article focuses on the correspondence between Lange and Steindorff in the years 1937-1939. These were landmark years for both men. After 13 years as a lecturer in Egyptology at the University of Copenhagen, 74-year-old H. O. Lange had retired on 1 July 1937, and Georg Steindorff, who was two years older at this point, had also retired after more than 40 years as Professor in Egyptology at the University of Leipzig. The correspondence clearly shows that during these years, on a personal and profession level, there was more at stake for Georg Steindorff. Despite the fact that he had already been baptised in 1885, according to National Socialist race laws, Steindorff continued to be considered as a “full Jew” (Volljude). However, and quite unusually, Steindorff was able to teach at the University up until the end of 1935. However, in the following years, he was increasingly persecuted by the Nazi regime. In 1937, he was forced to relinquish his many years as editor of the leading scientific journal, Zeitschrift für Ägyptische Sprache und Altertumskunde, which brought to an end his status as the profession’s grand old man in Germany. In December 1938, he was forced to withdraw from the Saxon Scientific Academy and, at the end of March 1939, he emigrated with his wife to the USA. The correspondence between the two old friends and colleagues apparently ended abruptly in the autumn of 1939. Personal reasons are not thought to be the cause of this breakdown in communication; it was probably caused by the outbreak of the war. Central to H. O. Lange and Georg Steindorff’s correspondence during the period 1937-1939, was the question of how to safeguard Georg Steindorff’s unpublished scientific works and preserve them for the future. Steindorff was very much interested in giving them to H. O. Lange in Copenhagen, but the German Egyptologist ended up bringing them to the USA anyway. However, neither did his etymological Coptic-Egyptian glossary nor his planned thesis on ‘Achmimische Proverbien’ to be written with his deceased colleague, Carl Schmidt ever see the light of day. On the other hand, Steindorff’s Coptic grammar was published posthumously in 1951 under the title Lehrbuch der koptischen Grammatik. Nor did H. O. Lange, who in January 1939 had expressed his hope that Steindorff would be fortunate enough to finish this important work, get to see the finished results. On 15 January 1943, the Danish Egyptologist died at the age of 79.